John Ford's stagecoach - Grant, Barry Keith, 1947- (Cambridge film handbooks series., 2003)
Stagecoach is one of the classics of Hollywood cinema. Made in 1939, it revitalized the Western genre, served as a milestone in John Ford's career, and made John Wayne a star. This volume offers a rich overview of the film in essays by six leading film critics. Approaching Stagecoach from a variety of critical perspectives, they place the film within the contexts of authorship, genre, American history and culture. Also examined are the film's commentary on race, class, gender and democracy, while remaining attentive to the film's artistry.